Regio- and Diastereoselective Samarium-Mediated Allylic Benzoate Reductions - Stockdale, Trevor F.; O’Neil, Gregory W. (Synlett, 2017)
A regio- and diastereoselective samarium(II)-mediated reduction of allylic benzoates is described. Yields for the reactions are generally high with diastereoselectivities up to 90:10 and in some cases only a single regioisomer was obtained. The stereoselectivity of the reaction is proposed to arise from chelation of a hydroxyl-stereocenter and starting alkene geometry, with protonation occurring intramolecularly by samarium-bound water.
Keywords: samarium; reduction; stereoselective synthesis; regioselectivity; diastereoselectivity